Field-based and molecular evaluation of anthelmintic resistance in gastrointestinal strongyle nematodes of meat goats in Southern Thailand - Narin Sontigun; Chalutwan Sansamur; Tunwadee Klong–klaew; Raktham Mektrirat; Morakot Kaewthamasorn; Punpichaya Fungwithaya (Veterinary World, 2025)
Background and Aim: are major health threats in goats, exacerbated by growing anthelmintic resistance (AR). Despite the widespread use of albendazole and ivermectin in Nakhon Si Thammarat, Southern Thailand, data on AR status in goats remain scarce. This study aimed to evaluate the resistance of GINs to albendazole and ivermectin using fecal egg count reduction (FECR) tests and to determine benzimidazole (BZ) resistance through molecular detection of the F200Y mutation in the β-tubulin isotype 1 gene. Materials and Methods: third-stage larvae, pre- and post-albendazole treatment. Results: (88.6%-100%), which reached 100% post-treatment. Susceptible genotypes were entirely eliminated following albendazole treatment. Conclusion: This is the first comprehensive study confirming widespread AR to albendazole and ivermectin in meat goats in southern Thailand. The fixation of the BZ resistance allele in both nematode species highlights the urgency for revising current deworming practices. Immediate adoption of integrated parasite management strategies, including drug rotation, targeted selective treatment, and exploration of alternative anthelmintics, is critical to mitigate economic losses and protect public health.
Keywords: Helminth infection and control; Parasitic Diseases Research and Treatment; Parasites and Host Interactions